Reduction of DNA damage repair efficiency and accumulation of residual damage following chronic UVB-irradiation of HaCaT cells. - Marie M Dorr; Patrick J Rochette (PLoS ONE, 2023)
Absorption of ultraviolet radiation (UVR) by DNA leads to the predominant formation of cyclobutane pyrimidine dimers (CPD). Since those CPD are responsible for the driver mutations found in skin cancers, their efficient repair is critical. We previously showed that pre-stimulation of fibroblasts with chronic low doses of UVB (CLUV) increases CPD repair efficiency. Since skin cancers are not arising from dermal fibroblasts, this observation is not directly relevant to cutaneous carcinogenesis. We have now exposed HaCaT keratinocytes to a CLUV irradiation protocol to determine whether this pre-stimulation influences CPD removal rate. Similar to fibroblasts, CLUV treatment leads to the accumulation of residual CPD in keratinocytes, which are not repaired but rather tolerated and diluted through DNA replication. In contrast to fibroblasts, in keratinocytes we find that CLUV pre-treatment reduces CPD removal of newly generated damage without inducing a higher sensitivity to UVR-induced cell death. Using our experimental data, we derived a theoretical model to predict CPD induction, dilution and repair that occur in keratinocytes when chronically UVB-irradiated. Altogether, these results suggest that the accumulation of unrepaired CPD and the reduction in repair efficiency caused by chronic UVB exposure might lead to an increase in skin cancer driver mutations.